SENI TRADISI DAN FOLKLOR SEBAGAI SUATU ELEMEN PENDUKUNG DATA ARKEOLOGIS DALAM MENCARI HARIJADI SEBUAH KOTA/ WILAYAH (STUDI KASUS DI PASURUAN, JAWA TIMUR) - Hari Lelono (BRIN, 2003)
Data and information in the form of art, traditions and folklore are supporting references, because usually there are archaeological objects, usually information in the form of stories, histories of certain figures related to the site. This information is very important in order to add to the arguments that will be presented in the seminars forum with local government officials and council members. Data in the form of speech, art and traditions can also be written as local historical content for the region concerned.